2013
DOI: 10.1002/jbmr.2041
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Dietary Carotenoids on Risk of Hip Fracture in Men: The Singapore Chinese Health Study

Abstract: Experimental and epidemiologic data suggest that carotenoids in vegetables and fruits may benefit bone health due to their antioxidant properties. The relationship between dietary total and specific carotenoids, as well as vegetables and fruits, and risk of hip fracture was examined among Chinese in Singapore. We used data from the Singapore Chinese Health Study, a prospective cohort of 63,257 men and women who were of ages 45–74 years between 1993 and 1998. At recruitment, subjects were interviewed on lifesty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 64 publications
3
86
1
Order By: Relevance
“…No significant associations were observed with other carotenoids. Data from other cohorts support the link between individual carotenoids and reduction of hip fracture risk [34]. Specific to lycopene, restriction studies of lycopene have shown significant increases in oxidative stress parameters and the bone resorption marker N-telopeptide of type I collagen in postmenopausal women, which were reversed with lycopene supplementation [35, 36].…”
Section: Fruit and Vegetable Intakementioning
confidence: 98%
“…No significant associations were observed with other carotenoids. Data from other cohorts support the link between individual carotenoids and reduction of hip fracture risk [34]. Specific to lycopene, restriction studies of lycopene have shown significant increases in oxidative stress parameters and the bone resorption marker N-telopeptide of type I collagen in postmenopausal women, which were reversed with lycopene supplementation [35, 36].…”
Section: Fruit and Vegetable Intakementioning
confidence: 98%
“…These studies have yielded a range of different results with some identifying an association between poor bone health and either low serum retinol (42)(43)(44)(45) or excess vitamin A (4-10, 46), or no difference between study groups (47)(48)(49)(50)(51)(52)(53)(54)(55)(56). For a detailed review see Conaway et al (57).…”
Section: A Number Of Cross Sectional and Longitudinal Studies Have Asmentioning
confidence: 99%
“…This study is the first to examine weight change in relation to risk of hip fracture in lean participants with BMI <20 kg/m 2 , which is an independent risk factor for hip fracture [14, 15]. We found that weight loss ≥10%did not further affect the risk of hip fracture among these lean individuals whose baseline BMI was already <20 kg/m 2 .…”
Section: Discussionmentioning
confidence: 93%
“…We used BMI <20 kg/m 2 as the cutoff for leanness, because it was a significant risk factor for hip fracture in this cohort [15] as well as in a meta-analysis that examined BMI and fracture risk [14]. We used the current recommendation by the World Health Organization of BMI ≥25 kg/m 2 as the cutoff for the overweight category [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation